OPTIMALISASI PRODUKSI AYAM BROILER DENGAN MENGGUNAKAN GOAL PROGRAMMING (Studi Kasus : Peternakan Mitra Sinar Jaya (MSJ) di Umalelu, Desa Aebubu Kecamatan Paga, Kabupaten Sikka) - Lindrawati Alberta Nanci; Faustianus Luan; Oktovianus Sikas; Fried Allung Blegur (Program Studi Matematika, Universitas Timor, 2025)
Mitra Sinar Jaya's Broiler Chicken Farm in Umalelu, Aebubu Village, Paga District, Sikka Regency, is an example of a livestock business that seeks to increase production and profits. Owners face difficulties to optimize various production components, including DOC, feed, medicines, husks, labor, cage capacity, and electricity use. The purpose of this study is to optimize the use of production factors to achieve maximum production and maximize profits. To optimize production factors and maximize profits, a method is used, namely Goal Programming assisted by lingo software. Based on the results of this study, it shows that cage 1 is more efficient in achieving the production target than cage 2, so that resource allocation is more directed to cage 1. The needs of Broiler Chicken production factors are DOC input of 5154 heads, feed use of 7731 Kg, use of 52 sacks of husks, use of electricity 2072 KwH, use of medicines 5051 grams, labor force of 2 people, cage capacity of 5154 heads. With a profit reaching Rp98,584,400.00 per harvest cycle.